Artificial intelligence applications in ODR: online dispute resolution: the UMCourt project - Andrade, Francisco Carneiro Pacheco (2010)
The growing use of electronic contracting urges the move of dispute resolution to online environments. Thus being, the technological element has to be considered as the “fourth party”. In this sense, software agents may well play an important role. One major issue in dispute resolution is the estimation of BATNA and of WATNA; software agents may become very useful tools in this operation, facing dispute resolution under a risk oriented approach. Having this in mind, it was developed UM COURT – based on which a concrete application, in the domain of Consumer’s Law, is presented here.